2020
DOI: 10.1371/journal.pone.0244072
|View full text |Cite
|
Sign up to set email alerts
|

High-risk pregnancies and their association with severe maternal morbidity in Nepal: A prospective cohort study

Abstract: Background The early identification of pregnant women at risk of developing complications at birth is fundamental to antenatal care and an important strategy in preventing maternal death. This study aimed to determine the prevalence of high-risk pregnancies and explore the association between risk stratification and severe maternal morbidity. Methods This hospital-based prospective cohort study included 346 pregnant women between 28–32 gestational weeks who were followed up after childbirth at Koshi Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 58 publications
3
26
0
1
Order By: Relevance
“…In this study, one third was registered as having a high-risk pregnancy in their antenatal cards, mainly due to advanced maternal age (16.8%) and teenage pregnancy (5.4%) as de ned ≤16 years old in national guidelines. This is in accordance with the 10% to 30% rate reported worldwide of pregnancies estimated to be "at-risk" [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, one third was registered as having a high-risk pregnancy in their antenatal cards, mainly due to advanced maternal age (16.8%) and teenage pregnancy (5.4%) as de ned ≤16 years old in national guidelines. This is in accordance with the 10% to 30% rate reported worldwide of pregnancies estimated to be "at-risk" [15].…”
Section: Discussionsupporting
confidence: 91%
“…Most evidence for using age and parity as risk criteria comes from studies of perinatal mortality but increased risk has also been demonstrated for women at the extremes of the fertile age range nulliparae or grand multiparae [42]. Women with risk factors for high-risk pregnancies have a one in four chance of developing complications than those with a low risk of high-risk pregnancies who have nearly one in ten [15,42]. In this study, one third was registered as having a high-risk pregnancy in their antenatal cards, mainly due to advanced maternal age (16.8%) and teenage pregnancy (5.4%) as de ned ≤16 years old in national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The institutional birth rate of Province 1, where the Morang district is located, is 62% [ 24 ]. In Morang, 14.4% of pregnancies were high-risk pregnancies in 2020 [ 25 ]. The population living in the Morang district is heterogeneous and diverse.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of high-risk pregnancies in Nepal was 41.0% in 2000 [ 8 ], 24.6% in 2015 [ 9 ], and 14.4% in 2020 [ 10 ]. The maternal mortality ratio is 239 per 100,000 live births, the perinatal mortality rate was 31 per 1000 live births, and the neonatal mortality rate was 21 per 1000 live births in 2016 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%